Law Students Understanding of the Principle of the Rule of Law in Indonesia - Ramadhan, Wahyu; Yuliani, Sri; Firmansyah, Syarif (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to describe the level of students’ understanding of the principle of the rule of law in Indonesia among 47 first semester students of the Law Program at Universitas Panca Bhakti. The research employed a quantitative descriptive approach, with data collected through a closed ended questionnaire comprising three main indicators: supremacy of law, equality before the law, and fair law enforcement. The data were analyzed using descriptive statistical techniques to determine the students’ level of understanding. The results revealed that 30 students (63.83%) demonstrated a high level of understanding of the rule of law, 14 students (29.79%) were in the moderate category, and 3 students (6.38%) were in the low category. These findings confirm that the majority of students have a solid grasp of the fundamental concepts and values of the rule of law, although a small portion still requires improvement through more contextual and applied learning approaches. This study is expected to serve as a reference for law programs in strengthening learning strategies based on constitutional understanding and enhancing legal awareness from the early stages of legal education.